THE ENVIRONMENTAL PARAMETERS SUITABILITY FOR MULTISPECIES-BASED MARICULTURE IN PONGOK ISLAND WATERS, BANGKA BELITUNG - Adibrata, Sudirman; Pamungkas, Aditya; Priyambada, Agung; Wahidin, La Ode; Hidayat, Syahrin Imron (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Pongok Island possesses small islands surrounded by waters with some primary commodities of sea farming. Seeking appropriate locations for marine aquaculture is a careful planning step to acquire optimal results. The sustainability of sea farming areas should be set based on considering species for easy implementation. This research aimed to analyse the area's suitability for aquaculture activities of seaweed cultivation, rearing groupers, and lobsters in floating net cages, and pearl oyster farming. This research occurred from June to November 2022 in Pongok Islands, South Bangka Regency, Indonesia. The method used in this research consisted of parameters weighting and scoring for cultivating seaweeds, groupers, or lobsters utilizing floating net cages and pearl oysters. Sea water samples analysis was processed in the Marine Science Laboratory of Bangka Belitung University and PT Global Quality Analytical, Bogor – West Java. Collected data were then scaled based on expert justification of scaling priority on aquaculture suitability. The mapping area of sea farming locations based on potential resources was then determined using map software. This research indicates that cultivating seaweeds is recommended to be established in two stations, 1 (149.79 ha) and 2 (186.46 ha), that are very suitable (S1) and the suitable (S2) categories, respectively. Station 3 (325.41 ha) and 4 (4.11 ha) are grouped into very suitable (S1) categories for pearl oysters and groupers or lobsters using floating net cages, respectively. The total estimate for sea farming in the waters of Pongok Island is 665.77 ha. Allocating seawater spaces should be assigned for sustainable fishery management. Maps of area suitability for sea farming can obviate conflicts in seawater areas.